When Can We Safely Stop Luteal Phase Support in Fresh IVF Cycles? A Literature Review - Mizrachi, Yossi; Raziel, Arieh; Weissman, Ariel (Frontiers in Reproductive Health, 2020)
There is no consensus on the optimal duration of luteal phase support (LPS) in fresh IVF cycles. Although some clinicians withdraw LPS on the day of a positive pregnancy test, most clinicians continue its administration at least up to the 8th week of gestation. In this literature review, we included several randomized clinical trials comparing early and late cessation of LPS. Most studies have found no benefit in extended administration. These studies, however, were limited by their small sample size and selection bias. Until now, only a few attempts have been made to indicate when LPS can be safely stopped based on individual patient characteristics. In conclusion, the quality and quantity of the evidence regarding LPS duration in fresh IVF cycles is currently insufficient to justify early cessation in all patients. Individualization of LPS should receive high priority in future research.